The High Number of Marriage Dispensations in Religious Courts: A Systematic Review from the Perspective of Human Rights and Maqashid Syariah Jasser Auda - Irma Afifatul Mursyidah Irma Afifah; Martha Eri Safira (CV. Cognispectra Publishing, 2026)
The widespread practice of marriage dispensations in Indonesia, and the ease with which judges grant them, demonstrates the continued weakness of law enforcement, particularly in the private sphere. In Malang Regency, for example, 1,009 marriage dispensation cases were recorded in 2024, with 95% being granted. A similar pattern occurred in the Lumajang Religious Court (682 cases), the Tasikmalaya Religious Court (519 cases), and the Garut Religious Court (391 cases). This research is a systematic literature review using an integrative analytical framework between human rights and the maqashid sharia (Islamic principles) of Jasser Auda. The results indicate that the surge in dispensations and the ease with which they are granted reflect the weak enforcement of the marriageable age limit, potentially violating the rights to education, health, and child protection. However, in emergency situations, dispensations are understood as mitigation to avoid greater harm. The study concludes that dispensations can only be justified if they truly guarantee the benefit, justice, and welfare of children. The implications require responsive policies, strict monitoring mechanisms, and an integrative approach between human rights and maqashid sharia in handling dispensations.